¿Lucha de soberanías? Dimensiones hegemónica y contrahegemónica de los derechos humanos y jurisdicción complementaria de la Corte Penal Internacional (2012)
It has been mentioned that the complementary jurisdiction which defines the ICC prevents the exercise ofstate sovereignty. However, for state crimes as crimes against humanity, it can be argued that supplementaljurisdiction could eventually form a setback. This, among other reasons, because it is not consistent withthe logic of effective protection of legal interests of particular value to humanity, whose congruency wasestablished in the past, defining the concurrent jurisdiction of the international tribunals in Yugoslaviaand Rwanda.In these conditions it is interesting to check this phenomenon from the counter-establishment of humanrights, recognizing as Boaventura de Sousa Santos does, existence, linkages and implications of theforms of power in capitalist societies, like their deep messages concerning state crimes. This, even moreso when it has been established that the discussion of counter-hegemony, beginning with Gramsci andpartly developed by Sousa Santos under the perspective of domination of neoliberal globalization, callsfor a “new global social contract more caring and inclusive than today social contract crisis of Westernmodernity “(Bonet, 2010).